An exploration of social impact bonds as a social development strategy. A South African case study - Nhaitayi, Ropafadzo (Department of Social Development, 2025)
South Africa faces significant and complex socio-economic challenges, such as high levels of poverty, unemployment, income inequality, and incessant electricity supply shortages, the result of which is a negative impact on productivity and the economy, as well as the livelihoods of the most vulnerable people in the country (Erero, 2023; OECD, 2019; Mubangizi and Mubangizi, 2005). Traditional funding approaches for social development, such as funds from the Treasury and development aid, have yielded mixed results, prompting the need for innovative solutions. De Witt (2018) calls for the deployment of innovative financing mechanisms as a possible solution to traditional social development financing. This study considered one such innovative financing solution, namely Social Impact Bonds (SIBs). This exploratory qualitative research employed multiple case studies and examined the design and implementation of the two pioneering SIBs in South Africa, the Impact Bond Innovation Fund (IBIF) and Bonds for Jobs (B4J). Data collection involved face-to-face interviews and a focus group discussion with key stakeholders. Document analysis was also conducted to augment interview data. The data generated were analysed using a combination of NVivo 14, as well as an adaptation of Tesch's (1990) approach where data were coded and organised into themes, categories, and sub-categories. The study identified SIBs as a potential alternative to traditional funding; the findings showed that both case studies were successful, as they met their outcome targets, were able to demonstrate innovation, and were also able to repay investors. The research also found that several challenges were encountered in the design and implementation of the SIBs, including high costs, lengthy setup times, and the COVID-19 pandemic. Additionally, the lack of specific SIB legislation presented hurdles during design and implementation. The findings from this research demonstrate the potential that SIBs carry, as such the findings can be thought of as providing a roadmap of issues to consider when designing and implementing SIBs in South Africa. The research concludes by offering recommendations for further research and the design of future SIBs in South Africa, including the establishment of a supportive regulatory framework and streamlining the design and implementation process.